Exploring cultural factors contributing maternal mortality among pregnant women: an ethnographic study in the Banjarnegara community, Central Java, Indonesia - Sulistyorini, Dewie; Kako, Mayumi; Ehsanul Huq, K. A. T. M.; Shaluhiyah, Zahroh; Moriyama, Michiko (Frontiers in Global Women's Health, 2025)
BackgroundCultural beliefs and power relationships existing in family daily practices significantly influence the health behaviors and outcomes of pregnant women. The role of family hierarchy and shamanic practices in shaping maternal health behaviors. In rural Indonesian communities, limited access to education and health literacy among women and their families hinders informed decision-making, increasing the risk of maternal and neonatal complications and death. This study approach, informed by the Foucauldian view of power relationships within family dynamics, aimed to explore the cultural norms and daily practices that contribute to adverse pregnancy outcomes.MethodA qualitative ethnographic study was conducted in Banjarnegara, Indonesia. Seventy participants—including pregnant women, their husbands, health cadres, and midwives—were recruited from three Public Health Centers (PHCs). Data collection involved 12 focus group discussions (FGDs), field observations, and in-depth semi-structured interviews. Data was analyzed by utilizing discourse analysis that highlighting communication and interactions of pregnant women with family members and health cadres who are assigend to support the women. This study was reported according to the COnsolidated criteria for REporting Qualitative Research (COREQ).ResultsThematic using discourse analysis revealed three primary themes: 1) daily activities of pregnant women, 2) family hierarchy and power dynamics, and 3) cultural practices involving shamans during pregnancy. The most frequently coded subthemes were cultural food practices (48.6%); activity-related practices (37.1%); family dominance (28.6%); shamanic practices (15.7%); practices related to rest and sleep (14.3%); and lack of reproductive control (14.3%).ConclusionPregnant women were often subject to culturally driven food taboos and restrictive physical routines, heavily influenced by family hierarchies and power relationships existing in their families—particularly mothers-in-law and husbands. These influences extended to decisions about reproductive health and prenatal care, sometimes leading to unplanned pregnancies and unsafe practices. The role of shamans, while culturally significant, poses risks when traditional methods conflict with scientific standards of care. Strengthening communication between healthcare providers and families, promoting culturally sensitive education, and empowering women through targeted interventions are essential to improving maternal and neonatal outcomes in these communities.